IDENTIFIKASI BAHAN KIMIA OBAT SIBUTRAMIN HCl PADA JAMU PELANGSING YANG BEREDAR DI KOTA BATAM MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Mayefis, Delladari; Marliza, Hesti; Fadhil, Muhammad (Jurnal Riset Kefarmasian Indonesia, 2025)
Traditional medicine is a mixture of natural ingredients in the form of simplicia, animals, minerals, sarian or galenic. One form of traditional medicine is slimming herbal medicine. In slimming herbal medicine, medicinal chemicals are prohibited from being added to traditional medicine preparations because they harm health if used continuously. One of the medicinal chemicals that is often misused is sibutramine HCl. The aim of this research is to identify the chemical drug sibutramine HCl in slimming herbal medicine circulating in Batam City. The method used is a qualitative method using thin layer chromatography and a quantitative method using UV-Vis spectrophotometry. The ferrous phases used are ethyl acetate : n-Hexane (7:3), acetone : chloroform (7:3), acetone : chloroform : n-hexane (5:3:2) and the stationary phase used is GF254 silica gel plate . The results of qualitative identification of slimming herbal medicine circulating in Batam City showed that there was no chemical drug sibutramine HCl in each sample. Quantitative testing was not carried out because there were no samples that were positive for containing the chemical drug sibutramine HCl